PERAN IBU RUMAH TANGGA PEKERJA BURUH KASAR DALAM MENINGKATAN KONDISI SOSIAL EKONOMI KELUARGA (Studi Pada PT. CAM Di Desa Bumi Raya Kecamatan Andoolo Kabupaten Konawe Selatan) - Irmawati, Irmawati; Rusli, Muhammad; Tawulo, Megawati Asrul (Universitas Halu Oleo, 2020)
This study aims to determine how the role of housewives of unskilled laborers at PT. CAM and to find out how the socioeconomic conditions of housewives who work at PT. CAM. This type of research is a qualitative descriptive study. The data collection technique was carried out by means of observation, interview and documentation with 7 housewives in Bumi Raya Village, Andoolo District who worked at PT. CAM. The results showed that the housewives of unskilled laborers at PT. CAM continues to carry out its duties as a housewife, namely caring for and educating her children, being her husband's partner, being a family manager, being a family finance minister, being a role model for her children, being a nurse for her family. And the socio-economic conditions of the family who work at PT. CAM is good enough, this is shown through indicators of meeting family needs / expenditure, income, housing but not for educational indicators where the education of housewives who work at PT. CAM is still relatively low, namely only elementary or junior high school graduates.